Mathematics
Domingueze18Ed
26

how do you solve y=2x+7; 3x-y=-9 using substitution method. Explain please!!

+2
(2) Answers
trav1ty

The y's value is given in the first equation. [latex]y=2x+7[/latex] . Now to solve, we will, plug it's value in the second equation. [latex]3x-(2x+7)=-9\\ \\ 3x-2x-7=-9\\ \\ x=-9+7\\ x=-2\\ [/latex] Now we have x's value, we will plug it's value in the first equation.(We can plug it in the second one too, but plugging it the first one will make it easier.) [latex]x=-2\\ y=2x+7\\ y=2\cdot -2+7\\ y=-4+7\\ y=3[/latex]

Hantula537

{ y = 2x + 7 { 3x - y = - 9 Substitute y for 2x + 7 in the 2nd equation: 3x - y = - 9 3x - ( 2x + 7 ) = - 9 3x - 2x - 7 = - 9 3x - 2x = - 9 + 7 x = - 2 Substitute - 2 for x in one of the equations: y = 2x + 7 y = 2.( - 2 ) + 7 y = - 4 + 7 y = 3 S = { - 2 , 3 }

Add answer